Hydatid Cyst in Orbit- Imaging Presentation with Surgical and Histopathological Correlation - Asma Javed; Bilquees Yawar; Fatima Moin; Saadur Rehman (Journal of the Dow University of Health Sciences, 2021)
Hydatid cyst is a common parasitic disease found mostly in developing countries, causing diagnostic and therapeutic challenges to the radiologists and physicians. Orbital hydatid is quite rarely reported in literature (<1%). Care should be taken pre-operatively to avoid the risk of rupture since surgery remains the ultimate treatment choice. We present imaging findings of orbital hydatid cyst on magnetic resonance imaging. This was confirmed on histopathology after complete surgical resection.